Some Computational Formulas for D-Nörlund Numbers - Guodong Liu (Abstract and Applied Analysis)
The author establishes some identities involving the D numbers, Bernoulli numbers, and central factorial numbers of the first kind. A generating function and several computational formulas for D-Nörlund numbers are also presented.